Hepcidin Decreases Rotenone-Induced α-Synuclein Accumulation via Autophagy in SH-SY5Y Cells - Li, Meiqi; Hu, Jianan; Yuan, Xiaoyu; Shen, Lihua; Zhu, Li; Luo, Qianqian (Frontiers in Molecular Neuroscience, 2020)
Parkinson’s disease (PD) is a neurodegenerative disorder, and the hallmarks of this disease include iron deposition and α-synuclein (α-syn) aggregation. Hepcidin could reduce iron in the central and peripheral nervous systems. Here, we hypothesized that hepcidin could further decrease α-syn accumulation via reducing iron. Therefore, rotenone or α-syn was introduced into human neuroblastoma SH-SY5Y cells to imitate the pathological progress of PD in vitro. This study investigated the clearance effects of hepcidin on α-syn induced by a relatively low concentration of rotenone exposure or α-syn overexpression to elucidate the potential clearance pathway involved in this process. We demonstrated that SH-SY5Y cell viability was impaired after rotenone treatment in a dose-dependent manner. α-Syn expression and iron content increased under a low concentration rotenone (25 nM for 3 days) treatment in SH-SY5Y cells. Pre-treatment with hepcidin peptide suppressed the abovementioned effects of rotenone. However, hepcidin had no effect after treatment with rotenone under high iron conditions. Hepcidin also played a role in reducing α-syn accumulation in rotenone and α-syn overexpression conditions. We identified that the probable clearance effect of hepcidin on α-syn was mediated by the autophagy pathway using pretreatment with autophagy inhibitors (3-MA and CQ) and detection of autophagy protein markers (LC3II/I and p62). In conclusion, hepcidin eliminated α-syn expression via the autophagy pathway in rotenone-treated and α-syn overexpression SH-SY5Y cells. This study highlights that hepcidin may offer a potential therapeutic perspective in α-syn accumulation diseases.